Comparison of Total Suspended Particulate (TSP) Measurement in Urban and Suburban Areas of Bali during Nyepi Day 2015 - Tri Astuti Nuraini; Donaldi Sukma Permana; Ratna Satyaningsih; Rian Anggraeni; Edvin Aldrian (Universitas Muhammadiyah Surakarta, 2019)
Nyepi or the Balinese Day of Silence (DOS) is a day when people celebrate every New Year according to the Balinese calendar (Saka). On that day, all resident activities were very restricted, with no outdoor activities. This event, which only lasted for 24 hours, is a unique period to conduct air quality measurements such as Total Suspended Particulate (TSP) for assessing the influence of human activities. This study only focuses on TSP monitoring before, during and after the DOS and its comparison with the meteorological data. TSP concentration measurements were conducted in 2 urban areas (Badung and Ubung) and a sub-urban area (Singaraja) from March 17 to March 25, 2015. The results show that TSP concentrations are negatively correlated with temperature and wind speed at each location. Hourly TSP concentrations during DOS are lower than the averaged TSP concentrations before and after DOS. During DOS, TSP concentrations decreased significantly in urban areas by 73-78% relative to regular days, which is likely due to drastically decreasing of human activities. In suburban areas, the decrease of TSP concentration was about 59%. These results show that human activities highly influence the air quality.